Morphological Structure of Polystyrene Degradated by Soil Bacteria from Sarimukti Final Landfill Cipatat Bandung - Tri Rahayu Hidayat; Ida Indrawati; Tati Herlina (International Journal of Science and Society, 2019)
The amount of Styrofoam waste in Bandung reaches 27,02 tons per month. Styrofoam used as packaging food or drinks, that are formed on styrene and benzene. The migration of benzene from packaging materials to food can cause various diseases. The most potent source of finding indigenous bacteria that can degrade of synthetic polymers is in the Final Landfill. This research method uses exploratory methods that are analyzed descriptively consisting of the stages of the biodegradation test with the Winogradsky Column method, calculation of the percentage of weight loss of Styrofoam, physical analysis with Scanning Electron Microscope (SEM). The results of this study found 4 species of polystyrene degrading bacteria is Pseudomonas aeruginosa, Bacillus amyloliquefaciens, Bacillus cereus and Bacillus firmus. The percentage reduction in dry weight of polystyrene showed in the first week the polystyrene weight decreased by 8.27% and increased weight loss up to the eighth week which reached 18.23% and and physical analysis with Scanning Electron Microscope (SEM) indicates that the process of degradation by soil bacteria showed the formation of holes or pores on the surface. These polystyrene degrading bacteria from Sarimukti landfills can be recommended as an environmentally friendly method for reducing styrofoam waste.